Design and development of a customised knee positioning orthosis using low cost 3D printers. Issue 4 (2nd October 2017) - Santos, Sara; Soares, Bruno; Leite, Marco; Jacinto, Jorge
ABSTRACT: Off-the-shelf orthoses used in rehabilitation medicine present challenges in the lack of individual comfort offered and in the support of the different motor conditions of the affected individuals. Although custom-made orthoses address these issues, their current fabrication method consists of a laborious and material wasteful process performed by skilled orthotists. Combining 3D scanning, 3D modelling and 3D printing, this paper proposes and assesses a method for the fabrication of custom-made products for rehabilitation medicine. In collaboration with CMRA, a Hospital dedicated to rehabilitation, the method is applied to the design of a customised knee positioning orthosis for a patient with cerebral palsy. This project is exploratory on the capabilities of the use of 3D printing in patient specific customisation of orthoses. Having developed, prototyped and tested four different concepts with the patient, from which one was successfully accepted, it is possible to demonstrate the potential of industrialisation of these technologies.